2020
DOI: 10.30602/jkk.v6i1.503
|View full text |Cite
|
Sign up to set email alerts
|

Efektifitas Pemberian Jus Jambu Biji Terhadap Perubahan Kadar Hemoglobin Pada Remaja Putri Di Pondok Pesantren Nurul Jadid Kumpai Kabupaten Kubu Raya

Abstract: Anemia adalah keadaan dimana kadar hemoglobin lebih rendah dari nilai normal. Vitamin C dapat meningkatkan pH didalam lambung sehingga dapat meningkatkan proses penyerapan zat besi hingga 30%. Kandungan vitamin C pada jambu biji sanggup memenuhi kebutuhan harian anak berusia 13 s/d 20 tahun yang mencapai 80 s/d 100 mg per hari, atau kebutuhan vitamin C harian orang dewasa yang mencapai 70 s/d 75 mg per hari. Untuk mengetahui efektifitas pemberian jus jambu biji terhadap perubahan kadar hemoglobin pada remaja p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…This study is consistent with the results of Damayanti (2020), who found differences in hemoglobin levels between groups who received iron tablets and those who consumed guava juice. 20 Additionally, this study is consistent with studies done on anemic pregnant women who were given vitamin C. There was a significant increase in hemoglobin levels. 21 This study is supported by other studies, namely, the provision of iron supplements also affects the increase in iron in pregnant women who experience anemia with p<0.05.…”
Section: Discussionsupporting
confidence: 90%
“…This study is consistent with the results of Damayanti (2020), who found differences in hemoglobin levels between groups who received iron tablets and those who consumed guava juice. 20 Additionally, this study is consistent with studies done on anemic pregnant women who were given vitamin C. There was a significant increase in hemoglobin levels. 21 This study is supported by other studies, namely, the provision of iron supplements also affects the increase in iron in pregnant women who experience anemia with p<0.05.…”
Section: Discussionsupporting
confidence: 90%
“…Perhitungan sampel menggunakan rumus Sastroasmoro (2014) yang didapatkan hasil dengan derivat baku alfa 95% (Z α = 1,96) atau α = 0,05 dengan derivat baku beta 90% (Z β = 1,28) (Sastroasmoro, 2014;Damayanti et al, 2020). Pada akhirnya didapatkan 36 subjek yang terbagi dalam 3 kelompok yaitu 12 subjek kelompok kontrol (tablet tambah darah), 12 subjek kelompok P1 (tablet tambah darah + jus jambu biji merah), 12 subjek kelompok P2 (tablet tambah darah + jus jambu kristal).…”
Section: Penelitian Ini Dilakukan DI Pondok Pesantrenunclassified